Are green bonds relevant to retail investors? Evidence from Robinhood - Hermanns, Emma Luise (2022)
Do retail investors care about green bonds? I show that retail investors care no more and no less about green bonds than they do about conventional bonds. On a single event level, there is evidence of mixed reaction towards the issuance announcement. Furthermore, the market reacts negatively to green bond announcements so that retail investors make losses by holding the underlying stocks.